Nursing experiences of COVID‐19 outbreak in Iran: A qualitative study - Ahmad Kalateh Sadati; Leila Zarei; Saeed Shahabi; Seyed Taghi Heydari; Vajihe Taheri; Razieh Jiriaei; Najme Ebrahimzade; Kamran Bagheri Lankarani (Wiley, 2021)
Abstract Aim The global outbreak of coronavirus in 2020 was considered as a serious risk for healthcare providers, especially nurses. This study aimed to investigate nurses' perceptions and experiences of COVID‐19 outbreak in Iran. Design This thematic analysis study was conducted in March 2020. Method Semi‐structured interviews were conducted with 24 nurses in Qazvin, Arak, Shiraz and Kashan cities of Iran. Results It was found out that all the participants had faced a mysterious world created by the virus. No one had clear understanding of the new virus and knew how to tackle with such a virus. In this case, the main experiences were related to defected preparedness, the worst perceived risk, family protection, social stigma and sacrificial commitment. Urgent preparedness of facilities in such outbreaks is inevitable. Accordingly, psycho‐social support of nurses and their families and strengthening their sacrificial commitments are proposed in these conditions.